Molecular characterization of bovine CD26 upregulated by a staphylococcal superantigen - Sang-Un Lee; Young-Ho Park; Davis, W.C.; Hamilton, M. Jo; Naessens, Jan; Bohach, G.A. (Springer, 2002)
In this report, we describe the cloning, sequencing, and expression of the bovine orthologue of CD26 (BoCD26). Several monoclonal antibodies specific for a molecule, activation molecule 3 (ACT3), aberrantly expressed on superantigen-stimulated bovine CD8+ lymphocytes, reacted with recombinant BoCD26 expressed in COS-7 and CHO cells. We also showed that human CD8+ T cells stimulated by a superantigen expressed CD26 at high levels. These results demonstrate that ACT3 is identical to BoCD26 and suggest that CD26 upregulation on CD8+ T cells is a general phenomenon of superantigens and not limited to their effects on bovine cells.